Effectiveness of Nursing Preventive Interventions in Suicide re- Attempts - B Ghanbari; SK Malakouti; M Nojomi; K Alavi; SH Khaleghparast; A Sohrabzadeh (Iran University of Medical Sciences, 2016)
Abstract Background & Aims: Suicide is an important public health issue. An estimated 1530000 suicide deaths will occur worldwide in 2020. Providing the preventive programs is the main task of nursing. This study designed to determine the effectiveness of nursing preventive interventions in suicide reattempt. Material & Methods: The clinical trial method using randomization sampling method that has been conducted on patients with suicide attempt(Maclure, 2000 #329;Maclure, 2000 #329). This study conducted on 248 people who attempted suicide and were referred to Baharloo hospital in Tehran, Iran since July to October 2013. The demographic characteristics questionnaire and discharge follow-up questionnaire used for data collection. To analyze the data, SPSS version 16 was used. Results: In this study, out of a total of 248 attempts to commit suicide, woman, singles and unemployed compromised 66.1%, 52.8% and 43.5% of participants respectively. In the intervention group 8.5% of participants committed suicide once. In the control group participants had attempted suicide once (10.5%), twice (7.9%) or three time (3.3%). There was a significant relationship between the nursing preventive program and suicidal attempts (P <0.05). Conclusion: This study showed that nursing preventive programs play an important and significant role in suicide re-attempts prevention.